Treatment of primary cutaneous anaplastic large cell lymphoma - Baik, Bong Soo (Arch Craniofac Surg, 2019)
Primary cutaneous anaplastic large cell lymphoma (C-ALCL) is a rare subtype of primary cutaneous lymphoma with a favorable prognosis. Primary cutaneous CD30+ lymphoproliferative disorders, which include C-ALCL and lymphomatoid papulosis, are the second most common group of cutaneous T-cell lymphomas. C-ALCL is comprised of large cells with anaplastic, pleomorphic, or immunoblastic cytomorphology, and indeed, more than 75% of the tumor cells express the CD30 antigen. C-ALCL clinically presents with solitary or localized reddish-brown nodules or tumors, and sometimes indurated papules, and they may be with ulceration covering with dark eschar. Multifocal lesions are seen in 20% of the patients. Extracutaneous dissemination, which mainly involves the regional lymph nodes, occurs in 10% of patients. A 69-year-old man noticed a mild elevated cutaneous lesion containing central ulceration covering with brownish black necrotic tissue on the right lower lip, and the lesion was surgically removed. After the first operation, another skin lesion was developed and the histological examination confirmed the diagnosis, C-ALCL. Eight specimens were excised during the 7-month follow-up period. The patient started the treatment with low-dose oral methotrexate (15 mg/wk) and there was no recurrence for 11 months.